The appropriateness of capitalisation, impairment and write-off on the intangible asset expenditures in the oil and gas accounting - a study on a prominent oil and gas organisation / Nurul Farhana Mohd Ami - Mohd Ami, Nurul Farhana (2013)
One of the possible ways to grasp a quick understanding on how oil and gas accounting works at the surface is to provide some rationalisations in mastering the treatments of capitalisation, impairment and write-off of the Intangible Assets.Adjustments towards Intangible Assets thus by far is one of the most critical aspects in recognising and realising how intricate oil and gas accounting can be. Having to manage the book of accounts in one of the prominent oil and gas organisation can indeed give a difficulty to anyone. That is of course, to have a set of objectives that the financial statements must be accurate in terms of true and fair view is a concern for every individuals and the related parties as a whole. Thus, this research will provide insights on how the accounting adjustments of Intangible Assets are being practiced in the studied oil and gas organisation and how their current procedures overcome the obstacles of having to identify and to treat billions of expenditures appropriately in the span of the Intangible Assets. The objectives of this research paper are to (i) ascertain the importance of choosing effective accounting method for capitalisation, impairment and write-off of Intangible Assets in oil and gas accounting, (ii) to evaluate the current accounting practices on Intangible Assets of the prominent oil and gas organisation and (iii) to identify any problems in the current accounting practices of the organisation and its approaches in alleviating the problems. This research paper is based on the primary data retrieved from the personal observation on the accounting treatments, interview sessions with experienced finance operation managers and questionnaires responded by participants from various working levels in the organisation. The study provides vital information to the field of oil and gas accountants in particular on how to manage the accounting treatments of Intangible Assets in rightful manner